Customer Value, Satisfaction and Behavioral Intentions: the Effects of Consumer Search Behavior - Wahyuningsih, Wahyuningsih (UI Scholars Hub, 2021)
This study develops and tests an integrative model to examine the relationships among customer value, satisfaction and behavioral intentions based upon a typology of consumer search behaviors. The model was tested using surveyed data from 546 customers of car insurance in Melbourne, Australia. The findings demonstrate that each type of consumer (passive, rational-active, relational-dependent), performs differently on the relationships among customer value, satisfaction, and behavioral intentions. The identification of value, satisfaction, and behavioral intentions within each search behavior allows managers to deliver optimal value and satisfaction to their consumers.